THE CREATIVE PROCESS IN SANDBURG'S "PRAYERS OF STEEL" - Rénaux, Sigrid (Revista Letras, 1982)
The aim of this analysis is to show how Carl Sandburg, one of the pioneers of "The Little Renaissance" in American poetry, was able to project, through his poem "Prayers of Steel", not only many characteristics of the new poetry but he succeeded in making the poem become iconic of the creative process the artist is passing through, while working on his work of art.